The Application Of Telerehabilitation To Post-Stroke Patients In The Covid-19 Pandemic Era - Magda Fiske Rumambi; Maria Maxmila Yoche Arkianti; Christie Lidya Rumerung (Jurnal Keperawatan Malang, 2023)
ABSTRACT Background: Stroke is a cerebrovascular disease that causes sudden death. The blockage causes a lack of oxygen supply which can cause rupture of the arteries to the brain and death of the cells. The COVID-19 pandemic has affected stroke care through various aspects, many of which are associated with neurological symptoms and complications that occur due to delays in treatment. Therefore, the application of telerehabilitation can help support and care for patients with stroke by reducing the risk of transmission of COVID-19. Purpose: The aim of this study was to analyse the application of telerehabilitation to post-stroke patients during the COVID-19 pandemic. Method: The research method is in the form of a literature study with literature search using an online database, namely PubMed, Medline, and Google scholar with a range year of 2019 to 2021. The number of articles found was 889 articles with four papers that met the inclusion criteria. Results: The results of this study indicate that telerehabilitation is effective for stroke patients, but providing telerehabilitation must pay attention to the patient's and family's ability to use digital technology, the ability to understand rehabilitation programs, and also various aspects such as functional status: direct motor skills involving the upper extremities, balance, cardiorespiratory fitness, cognitive function, and the level of acceptance and eligibility of teletherapy by users (patients/families) at home so that the therapy program can run optimally. Conclusion: Telerehabilitation is effectively implemented in the era of the COVID-19 pandemic because it can provide support and help patients, families, and health services in providing care for stroke patients while reducing the risk of transmission of COVID-19. Keywords: Stroke; Pandemic; COVID-19; Telerehabilitation